Immunogenetics of new onset diabetes after transplantation in Kuwait - Jahromi M (Dove Medical Press, 2019)
Mohamed Jahromi,1 Torki Al-Otaibi,2 Nashwa Othman,3 Osama Gheith,2 Tarek Mahmoud,2 Prasad Nair,2 Medhat A Halim,2 Narayanam Nampoory1,21Clinical Research, Medical Division, Dasman Diabetes Institute, Kuwait City, Kuwait; 2Nephrology Department, Hamid Al-Essa Organ Transplant Center, Kuwait City, Kuwait; 3Education, Clinical Services Division, Dasman Diabetes Institute, Kuwait City, KuwaitIntroduction and aim: New onset diabetes after transplantation (NODAT) is a serious metabolic complication following kidney transplantation. Although beta-cell dysfunction is considered the main contributing factor in the development of this complication, its exact etiology is yet to be identified. We aimed to investigate NODAT among kidney transplant cohort in Kuwait with special stress on correlation between its risk factors and interferon gamma genotyping.Materials and methods: We surveyed 309 kidney transplant recipients from Hamed Al Essa Transplantation Centre, Kuwait. The participants were categorized into cohorts according to the development of NODAT diagnosed based on the American Diabetes Association guidelines. Statistical analyses were performed using SPSS software. We genotyped interferon gamma as the leading immunosignature for T lymphocyte.Results: No relationship between ethnicity and the development of NODAT was identified. However, there was a significant difference in age between cohorts. Younger patients demonstrated a lower rate of NODAT while, NODAT reached its maximum in 40–60-year age group. IFNG TT genotype was significantly associated with NODAT (p=0.005), while IFNG AA was considerably higher in the non-NODAT group.Conclusion: Beside the conventional contributing factors of NODAT, our results might represent a suitable platform for a larger cytokine and chemokine spectrum genotyping.Keywords: ethnicity, NODAT, transplantation, immunosuppression